How Has the Global Financial Crisis Affected Syndicated Loan Terms in Emerging Markets? Evidence from China - Guglielmo Maria Caporale; Suman Lodh; Monomita Nandy (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper examines the impact of the recent global financial crisis on the cost of debt capital (syndicated loans) in a leading emerging market, namely China, using difference-in-differences and GARCH approaches. Before the crisis China adopted banking reforms allowing entry of foreign banks and more domestic participation in the syndicated loan market. As a result, during the crisis the volume of syndicated loans grew steadily, in contrast to other countries. In addition, the amount of foreign syndicated loans decreased and average maturity increased compared to the pre-crisis period. Our findings provide useful information to policy makers to devise effective responses to financial crises.
Keywords: G21; G32; P34; 330; loan spread; loan amount; loan maturity; China; financial crisis